1992
DOI: 10.1007/bf00713939
|View full text |Cite
|
Sign up to set email alerts
|

The flocculation of wine yeasts: biochemical and morphological characteristics inZygosaccharomyces ? flocculation inZygosaccharomyces

Abstract: The floc-forming ability of flocculent strains of Zygosaccharomyces bailii and Z. fermentati, isolated from musts, was tested for susceptibility to proteinase and sugar treatments. Z. fermentati was found highly resistant to the proteolytic enzymes tested, whereas Z. baili was only trypsin-resistant. The inhibition of flocculation by sugars distinguished two types: in Z. fermentati flocculation was completely inhibited by mannose, in Z. bailli by various sugars. By SEM observation, the cell surface of Zygosacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It has been reported that anthocyanins participate in microbial metabolism, such as biotransformation, polymerization, copigmentation, oxidation, and flocculation adsorption with protein and phenolic compounds, during alcohol fermentation (Cecchini et al, 2019;Fan et al, 2019;F. He et al, 2012;Li, Teng, et al, 2022;Sun et al, 2022;Suzzi et al, 1992). C. Wu et al (2020) found that fermentation could accelerate biocatalysis of delphinidin-3-glucoside into polyphenols, and the intensity of transformation depended on the chemical structure of these compounds.…”
Section: Anthocyanins During Fermentationmentioning
confidence: 99%
“…It has been reported that anthocyanins participate in microbial metabolism, such as biotransformation, polymerization, copigmentation, oxidation, and flocculation adsorption with protein and phenolic compounds, during alcohol fermentation (Cecchini et al, 2019;Fan et al, 2019;F. He et al, 2012;Li, Teng, et al, 2022;Sun et al, 2022;Suzzi et al, 1992). C. Wu et al (2020) found that fermentation could accelerate biocatalysis of delphinidin-3-glucoside into polyphenols, and the intensity of transformation depended on the chemical structure of these compounds.…”
Section: Anthocyanins During Fermentationmentioning
confidence: 99%
“…Reasons for the onset of flocculation in brewer's yeast include nutrient or oxygen depletion and surface hydrophobicity (Straver et al, 1993a;. In recent years, it has ceased to be solely a concern of the brewing industry and flocculation has been reported in Kluyveromyces (Sousa et al, 1992), Zygosaccharomyces (Suzzi et al, 1992), S. diastaticus (Guiraud and Fontana, 1992), Pichia (Ferrari et al, 1992), Candida (Cubells Martinez et al, 1993) and Schizosaccharomyces .…”
Section: Aggregation: Mating and Flocculationmentioning
confidence: 99%
“…Flocculation is under genetic control [18], but cultural and nutritional conditions also play an important role in the expression of the flocculation phenotype [10]. The involvement of lectin or lectin-type proteins and carbohydrate receptors of the cell wall in flocculation was first demonstrated in Saccharomyces cerevisiae [7] and later in Kluyveromyces bulgaricus [4], Schizosaccharomyces pombe [5], Saccharomycodes ludwigii [14] and in Zygosaccharomyces strains [15]. Bivalent cations, preferably Ca 2+ , are a prerequisite for flocculation, their role being the reversible activation of lectins by ensuring the proper conformation [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…In some strains of Saccharomyces cerevisiae, mannose-specific lectins govern flocculation by interacting with the outer-chain mannan side-branches of the cell wall [13]. In a flocculent strain of Kluyveromyces bulgaricus, galactose-and N-acetyl glucosamine-specific lectins were isolated [1], while in Zygosaccharomyces fermentati a mannose-specific lectin was also involved in flocculation [15].…”
Section: Introductionmentioning
confidence: 99%